Teacher attitudes towards the inclusion of children with mild hearing impairments into the regular school settings - Maunganidze L., Kasayira Joseph M.; Ruhode, N.; Shonhiwa, L.; Sodi, T. (Routledge, 2021)
The study examined the attitudes of a sample of Zimbabwean teachers towards the inclusion of children with mild hearing impairments. Two hundred and forty-six primary school teachers participated in the study. The teachers completed the modified Attitude Toward Mainstreaming Questionnaire (ATMQ) (Larrivee & Cook, 1979). In addition, they also completed four measures on implementation concerns of inclusive education of children with mild hearing impairments (i.e., academic, management, social, and knowledge concerns). Analysis related the scores from these four measures to teachers' attitudes, school type, class sizes, professional qualifications and position in the school. Compared with teachers with lower professional qualifications, teachers with higher professional qualifications had more favourable attitudes towards children with hearing impairment. Teachers who taught at ordinary schools with special needs resource units had more favourable attitudes towards students with hearing impairment than those at schools without such units. Resource unit teachers welcomed social inclusion of children with mild hearing impairments. School administrators were concerned about the practice of including children with hearing impairments in regular school setting before inducting teachers.